Mechanisms of interaction between polystyrene nanoplastics and extracellular polymeric substances in the activated sludge cultivated by different carbon sources. (February 2023) - Wang, Yaxin; Liu, Xiuhong; Liu, Runyu; Han, Weipeng; Yang, Qing
Abstract: Nanoplastics (NPs) are ubiquitously present in wastewater treatment plants, which would be removed by the flocculation of extracellular polymeric substances (EPS) from activated sludge. However, the interaction mechanisms between NPs and EPS of activated sludge remain largely unexplored. This study investigated the interaction mechanisms between polystyrene nanoplastics (PS-NPs) and EPS with sodium acetate (NaAc), methanol (MeOH) and glucose (GLC) as carbon sources. The results showed that the functional group involved in the interactions between PS-NPs and EPS was the carbonyl of protein amide I region. The interaction between PS-NPs and EPS increased the β-sheets content, decreased the ratio of α-helix to (β-sheet + random coil), and changed the protein secondary structures to strong rigidity. This enhanced the flocculation of activated sludge cultivated by these three carbon sources. The flocculation between PS-NPs and EPS in activated sludge using NaAc as the carbon source was the strongest among these three carbon sources. Therefore, the degree of flocculation between NPs and EPS of activated sludge in wastewater treatment plants varies with carbon sources. This work provides a reference for the NPs removal mechanisms from wastewater, which will help to understand the migration behavior of MPs and NPs in wastewater treatment processes. Graphical abstract: Image 1 Highlights: The groups contained in the protein of EPS preferentially interacted with PS-NPs. The β-sheets played a vital role in the flocculation between EPS and PS-NPs. PS-NPs increased the contact surface area and promoted bioflocculation. NaAc had the best flocculation between EPS and PS-NPs among three carbon sources.